1999
DOI: 10.1139/g99-047
|View full text |Cite
|
Sign up to set email alerts
|

Development of the molecular methods for potato virus and viroid detection and prevention

Abstract: Potato is the fourth most important food crop in the world and it forms the diet of a billion consumers in developing countries, where potato production is increasing rapidly. However, potato virus diseases in developing countries are one of the major causes of lower yields. Their control requires the development of appropriate virus-detection and seed-production technologies for the region. Recent progress in developing nucleic acid based virus detection methods are reviewed. Refinements of the protocols appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 69 publications
0
5
0
3
Order By: Relevance
“…In the current study, all participants were young people (aged from 20 to 24), and the number of male participants was larger than that of female participants (Fisher's exact test; p = 0.04). It was reported that age and gender affect the average heart rate (Sagie et al, 1992;Singh, 1999;Mason et al, 2007). In further studies, getting data from various attribution participants could lead the results of the current study more reliable.…”
Section: Discussionmentioning
confidence: 64%
“…In the current study, all participants were young people (aged from 20 to 24), and the number of male participants was larger than that of female participants (Fisher's exact test; p = 0.04). It was reported that age and gender affect the average heart rate (Sagie et al, 1992;Singh, 1999;Mason et al, 2007). In further studies, getting data from various attribution participants could lead the results of the current study more reliable.…”
Section: Discussionmentioning
confidence: 64%
“…As técnicas de hibridização de ácidos nucleicos (dot-blot e Northern-blot) foram as primeiras a serem empregadas para identificar espécies de viroides (OWENS & DIENER 1981;SINGH 1999), incluindo polissondas capazes de detectar diversos pospiviroides simultaneamente (TORCHETTI et al 2012), ou mesmo para análises de hibridização de tecido vegetal "impresso" -tissue-blot (HOOFTMAN et al 1996). Há empresas que prestam serviços de diagnóstico de viroides, por meio de hibridização dot-blot com sondas específicas.…”
Section: Métodos E Estratégias De Diagnóstico Dos Pospiviroidesunclassified
“…Viral diseases are a major cause of degeneration of the potatoes and disqualification of seed tubers (Singh 1999;Whitworth et al 2006) and their control is strictly based on the production of healthy seed material (Wróbel and Wąsik 2013). For the last three decades health certification of seed tubers is performed by grow-out test.…”
Section: Introductionmentioning
confidence: 99%